Eksodus Independensi Hakim Mahkamah Konstitusi dalam Putusan Nomor 141/PUU-XXI/2023: The Exodus of Independent Constitutional Court Judges in Decision Number 141/PUU-XXI/2023 - Zubairi, Ach (UIN Kiai Haji Ahmad Sidiq Jember, 2025)
This scientific paper aims to explore the Constitutional Court (MK) Decision Number 141/PUU-XXI/2023, which sparked controversy regarding violations of the principles of judicial independence and judicial ethics of constitutional justices. To examine this issue, the researcher refers to Alexander Bickel’s theory of judicial independence as an analytical tool to assess the impact of the ruling, which altered the interpretation of the age requirement for presidential and vice-presidential candidates previously explicitly regulated in Article 169 letter q of Law Number 7 of 2017 on General Elections. The Constitutional Court granted an exception for experienced regional heads, even if they had not yet reached the minimum age of 40, thereby exceeding its authority in constitutional review. Additionally, there are allegations of a conflict of interest, as the decision was issued under the leadership of Chief Justice Anwar Usman, who has a familial relationship with the beneficiary of the ruling, Gibran Rakabuming Raka. The absence of a recusal mechanism in the decision-making process has raised concerns about the integrity and independence of the institution. The findings of this study indicate a legitimacy crisis within the Constitutional Court, potentially threatening constitutional supremacy in Indonesia. Therefore, this study recommends strengthening the code of ethics for judges, reforming the selection process, and enhancing public oversight mechanisms to ensure the Constitutional Court continues to function as an independent and trustworthy guardian of the constitution. Abstrak Karya ilmiah ini bertujuan untuk mengeskplor putusan Mahkamah Konstitusi (MK) Nomor 141/PUU-XXI/2023 yang memicu kontroversi terkait pelanggaran prinsip independensi dan etika yudisial hakim konstitusi. Guna mengeksplorasi kajian ini, peneliti mengacu pada teori independensi yudisial dari Alexander Bickel sebagai pisau analisis untuk menilai dampak putusan yang mengubah tafsir batas usia calon presiden dan wakil presiden, yang semula diatur secara eksplisit dalam Pasal 169 huruf q Undang-Undang Nomor 7 Tahun 2017 tentang Pemilu. MK memberikan pengecualian bagi kepala daerah berpengalaman meskipun belum mencapai usia minimal 40 tahun yang melampaui kewenangan pengujian konstitusionalitas. Selain itu, terdapat dugaan konflik kepentingan karena putusan tersebut dikeluarkan di bawah kepemimpinan Ketua MK, Anwar Usman, yang memiliki hubungan keluarga dengan pihak yang diuntungkan, yaitu Gibran Rakabuming Raka. Tidak adanya mekanisme pengunduran diri (recusal) dalam proses pengambilan keputusan ini menimbulkan keraguan terhadap integritas dan independensi lembaga. Temuan penelitian ini mengindikasikan krisis legitimasi Mahkamah Konstitusi yang berpotensi mengancam supremasi konstitusi di Indonesia. Oleh karena itu, penelitian ini merekomendasikan penguatan kode etik hakim, reformasi proses seleksi, serta peningkatan mekanisme pengawasan publik untuk memastikan Mahkamah Konstitusi tetap berfungsi sebagai penjaga konstitusi yang independen dan terpercaya.